The Tricyclic Antidepressant Clomipramine Increases Plasma Glucose Levels of Mice - Yumi Sugimoto; Kiyo Inoue; Jun Yamada (Elsevier, 2003)
ABSTRACT: Effects of the tricyclic antidepressant clomipramine on plasma glucose levels in mice were studied. Clomipramine at doses ranging 5 - 20 mg/kg elicited significant hyperglycemia in mice. Hyperglycemia elicited by clomipramine was not reduced by pretreatment with the 5-hydroxytryptamine (5-HT) depleter p-chlorophenylalanine. The 5-HT1/2/5/7-receptor antagonist methysergide and the 5-HT2A/2B/2C-receptor antagonist LY 53857 enhanced clomipramine-induced hyperglycemia, while the 5-HT1A/1B-receptor antagonist (-)-propranolol and the 5-HT3/4-receptor antagonist tropisetron did not affect it. The 5-HT2B/2C-receptor antagonist SB 206553 facilitated hyperglycemia induced by clomipramine, although the 5-HT2A-receptor antagonist ketanserin was without effect. Clomipramine-induced hyperglycemia was reduced by prior adrenalectomy. These results suggest that clomipramine induces hyperglycemia in mice by blocking the 5-HT2B and/or 5-HT2C receptors, which results in facilitation of adrenaline release.